Perbedaan Presasi Belajar Anak Obesitas dan Tidak Obesitas di Sekolah Dasar Kabupaten Jember - Sulistyorini, Lantin (Jurnal Keperawatan Soedirman, 2014)
The prevalence of obesity in children is constantly increasing worldwide. The incidence of overweight and obesity in children increased more than three times over the last thirty years. The purpose of this research is to analyze the relation of obesity in children with academic achievement. The research design is Comparative Study. The sampling used random sampling technique with the samples were 194 students. Data Analysis using the multiple logistic regression. Statistical tests showed significant differences in the academic achievement obesity in children with no obesity in children (p value = 0.00). The school especially the teachers should be more intensive in paying attention of the obese children in teaching and learning